A significant enhancement of bulk charge separation in photoelectrocatalysis by ferroelectric polarization induced in CdS/BaTiO3 nanowires. Issue 43 (3rd August 2021) - Jiang, Zhiqi; Xiao, Zhaohui; Tao, Zui; Zhang, Xu; Lin, Shiwei
Abstract : Efficient charge separation, in particular bulk charge separation (BCS), is one of the most critical factors in determining the performance of photoelectrochemical (PEC) water-splitting. Abstract : Efficient charge separation, in particular bulk charge separation (BCS), is one of the most critical factors in determining the performance of photoelectrochemical (PEC) water-splitting. The BCS enhancement of CdS/BaTiO3 (CdS/BTO) nanowires (NWs) in photoelectrocatalysis has rarely been reported. This paper describes a remarkable PEC properties promotion of the CdS/BTO NWs, which is confirmed to be a result of the enhanced BCS efficiency induced by the ferroelectric polarization. The vertical arrays of BTO NWs endow fast transfer of carriers. Meanwhile, CdS is decorated uniformly on the surface of BTO NWs, which ensures a wide range of light absorption. After two negative polarizations, the CdS/BTO NWs have successfully obtained a remarkable photocurrent density, achieving 459.53 μA cm −2 at 1.2 V( vs. RHE), which is 2.86 times that of the unpolarized sample. However, after two positive polarizations, the photocurrent density dramatically decreases to 40.18 μA cm −2 at 1.2 V( vs. RHE), which is merely 0.25 times the original value. More importantly, the photocurrent density reaches up to a prominent value of −71.09 mA cm −2 at −0.8 V( vs. RHE) after two successive negative polarizations, which is a 40.87 mA cm −2 enhancement with respect to the sample without poling. Significantly, at −0.8 V( vs. RHE), the BCS efficiency of the CdS/BTO NWs is as high as 91.87% after two negative polarizations. The effects of ferroelectric polarization on the PEC performance of CdS/BTO NWs have been systematically studied. The results demonstrate that ferroelectric polarization, especially negative polarization, results in an internal electric field to tune band bending of CdS/BTO NWs, thus prominently enhancing the PEC performance.